If a+b+c=0 then prove that a³+b³+c³=3abc
Answers
Answered by
33
Answer:-
We know,
a³ + b³ + c³ - 3abc = (a + b + c)(a² + b² + c² - ab - bc - ca)
Given that: (a + b + c) = 0.
Putting the value:-
a³ + b³ + c³ - 3abc = (a + b + c)(a² + b² + c² - ab - bc - ca)
→ a³ + b³ + c³ - 3abc = (0)(a² + b² + c² - ab - bc - ca)
→ a³ + b³ + c³ - 3abc = 0
→ a³ + b³ + c³ = 3abc
Hence, Proved.
Answered by
51
To prove:-
•If a+b+c=0,then a³+b³+c³=3abc
Solution:-
=>a+b+c=0
=>a+b= -c
=>(a+b)³=(-c)³
=>a³+b³+3ab(a+b)=-c³
=>a³+b³+3ab(-c)=-c³ (Since,a+b=-c)
=>a³+b³-3abc= -c³
=>a³+b³+c³=3abc
Thus,proved that-----
If (a+b+c)=0, then (a³+b³+c³)=3abc
Similar questions